En bristet drøm - til forståelse af Karl Emil Franzos’ forfatterskab - Riis, Carsten (Religionsvidenskabeligt Tidsskrift, 1989)
In a wide fictional and cultural historical authorship the Jewish Galizier Karl Emil Franzos (1848-1904) presented arguments for Jewish emancipation under the influence of the Haskalah movement. His chief work, Der Pojaz, is about a young East-Galizien Jew’s fight against the narrow limits of Hasidism and the aspirations about German culture. Der Pojaz was finished in 1893, but Franzos held it back, and it was first published posthumously in 1905. In his article Carsten Riis points out that the background for this must be found in the growing anti-Semitism during the second half of the 19th century – being the Germany that Franzos had seen as the new native country of the emancipated Jews. The anti-Semitism of the 19th century was the old traditional one, but the modern racist anti-Semitism had appeared, and this ruined Franzos’ hope and dreams of a new era for the Jews. In disappointment and powerlessness he withheld Der Pojaz and turned his authorship in other directions.